A Genetic Identification of Superbugs from River Streams in State University of Malang - Sholekah, Reeno Al Hikmatus; Listyorini, Dwi (Universitas Negeri Surabaya, 2023)
Superbugs revert to bacterial strains, which exhibit resistance to antibiotics. These bacteria could cause some problems in disease treatment and the environment. This research aimed of this study was to identify the presence of superbugs in the river stream that flows through Malang State University campus area. Amoxicillin, tetracycline, and chloramphenicol were selected to test the possible bacterial resistance. Water samples taken from a decided spot were spread over Luria Bertani’s agar on both antibiotic supplemented and antibiotics-free media with no delay. Molecular identification was carried out using 16S rRNA gene DNA barcoding approach, completed with morphological and Gram staining analyses. A total of 16 isolates of gram-negative colonies were found in the form of bacilli, diplobacilli, cocci, and diplococci. The genetic identification of eight resistant colonies led us to suggest that the isolates may belong to Aeromonas, Shigella, and Bacillus. Further studies are still required to get a clearer view of the correct taxonomical position of those resistant isolates.